Initation and intensification of east Pacific easterly waves - Rydbeck, Adam V., author; Maloney, Eric, advisor; Johnson, Richard, committee member; Birner, Thomas, committee member; Niemann, Jeffrey, committee member (Colorado State University. Libraries, 2015)
The background atmospheric state of the east Pacific (EPAC) warm pool in which easterly waves (EWs) develop varies dramatically on intraseasonal time scales. EPAC intraseasonal variability is well known to modulate local convective and circulation patterns. Westerly intraseasonal phases are associated with westerly lowlevel wind and positive convective anomalies and easterly intraseasonal phases are associated with easterly low-level wind and negative convective anomalies. This study first investigates the perturbation available potential energy (PAPE) and perturbation kinetic energy (PKE) budgets of easterly waves composited during westerly, easterly, and neutral intraseasonal phases, respectively. During neutral and westerly intraseasonal phases, the generation of PAPE associated with perturbation diabatic heating that is subsequently converted to PKE is enhanced and is the dominant energy source for EWs. EWs draw energy from low-level barotropic conversion, regardless of phase. A novel and previously unrecognized result is the detection of strong barotropic generation of PKE at midlevels during westerly intraseasonal phases. This previously unidentified source of PKE at midlevels is in part due to strong intraseasonal modulation of the background midlevel winds. Processes associated with the local amplification of EWs in the EPAC warm pool are then explored. Developing EWs favor convection in the southwest and northeast quadrants of the disturbance. In nascent EWs, convection favors the southwest quadrant. In these quadrants, lower tropospheric vorticity is generated locally through vertical stretching that supports a horizontal tilt of the wave from the southwest to the northeast. EWs with such tilts are then able to draw energy via barotropic conversion from the background cyclonic zonal wind shear present in the east Pacific. EWs during westerly and neutral intraseasonal periods are associated with robust convection anomalies. Easterly intraseasonal periods are, at times, associated with very weak EW convection anomalies due to weaker moisture and diluted CAPE variations. The in-situ generation of EWs in the EPAC is then investigated using the Weather Research and Forecasting Model (WRF). Sensitivity tests are performed to examine the atmospheric response to the removal of external and internal EW forcing in the EPAC warm pool. External forcing of EPAC EWs is removed by filtering EWs in wavenumber frequency space from the model’s boundary forcing. Internal forcing of EWs is removed by reducing the terrain height in portions of Central and South America to suppress the strong source of diurnal convective variability in the Panama Bight. These regions of high terrain are associated with mesoscale convective systems that routinely initiate in the early morning and propagate westward into the EPAC warm pool. In both sensitivity tests, EW variance is significantly reduced in the EPAC, suggesting that both EWs propagating into the EPAC from the east and EWs generated locally in association with higher frequency convective disturbances are critical to EPAC EW variability. A new mechanism is proposed to explain the in-situ generation of EPAC EWs. Serial mid-level diurnal vorticity and divergence anomalies generated in association with deep convection originating in the Panama Bight underpin the local generation, intensification, and spatial scale selection of EW vorticity by vertical vorticity stretching. Diurnal vorticity anomalies in the Panama Bight are able to initiate disturbances capable of growing into robust EWs through a tendency to organize vorticity upscale.
Keywords: easterly waves; intraseasonal variability; tropical waves